KONSEP PEMASARAN GLOBAL DAN IMPLIKASINYA BAGI INDONESIA - U. Maman Rubaman (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2003)
The old concept of marketing focused on (he product, and companies concentrated thin efforts on marking a "better” product. The objective was profit, and the means to achieving the objective was selling, or persuasing. The New concept of marketing shifted the focus of marketting from the product to the customer. The objective was still profit, but the means of achieving the objective Expanded to include the enttire marketing mix or the four P'S as they became known as product, price, promotion, and place. Another revolutionary change in the chift to strategic concept of marketing is the marketing objective, from profit to stakeholder - benefits. The marketig activitiesare the four P 'S plus research, and the marketing management proces is the task of focusing the resources and objective of organization upon opportunities in the environment. Comparative advantage concept change in the shift to man made comparative advantage concept or management comparative advantage. Indonesia must achieve the opportunities with direct export, via coordination with agent or distributor, or opening representation, in foreig.i countries. The are two ways for entry> into international market, vhich arecontractual. Example : licence, franchising, technical coordination, service contract, management contract, and production coordinate. Exactly, investment can be done through equisition, marger, and joint venture with foreigh companies.